Kidney replacement therapy trends in end-stage kidney disease patients in South Korea during the COVID-19 pandemic - Ah-Young Kim; Min-Jeong Lee; Heejung Choi; Hankil Lee; Inwhee Park (The Korean Journal of Internal Medicine)
Background/Aims The corona virus disease 2019 posed a major risk for end-stage kidney disease (ESKD) cases. Our study aimed to assess changes in kidney replacement therapy (KRT) trends and healthcare access for these patients during the pandemic. Methods We retrospectively analyzed nationwide data from July 2017 to June 2022 to assess changes in KRT and ESKD incidence. KRT modalities included peritoneal dialysis (PD), hemodialysis (HD), and kidney transplantation (KT). We utilized the interrupted time series (ITS) method to compare changes in KRT modality before and after the incidence of the COVID-19 pandemic. Results ESKD incidence remained stable from 2018 to April 2022. The ITS analysis confirmed that the pandemic did not significant impact overall KRT incidence. PD cases decreased (5.7% to 1.3%), while HD cases increased (81.6% to 85%), and KT recipient remained relatively stable (12.7% to 17.3%). The hospitalization and hospital stay decreased in nursing hospital (165.01 days to 147.77 days) and general hospital (61.34 days to 55.58 days) during the pandemic, however, remained unchanged for PD and KT. Conclusions Our findings indicate no significant changes in ESKD incidence in South Korea during the pandemic. However, there were shifts in modality distribution, with decreased PD and increased HD cases. Notably, HD cases showed a significant reduction in hospital admissions and length of stay. The healthcare system demonstrated stability during the pandemic, with minimal disruptions in ESKD care.